PERAN MEDIA SOSIAL DALAM PENYEBARAN INFORMASI DUGAAN KEKERASAN DALAM RUMAH TANGGA (KDRT) GUNA PENEGAKKAN HUKUM TINDAK PIDANA KDRT PADA ERA DIGITAL (Studi kasus perkara Nomor 52/PID.SUS/2025/PT BDG) - Yuni Sara; Punta Yoga Astoni (PT. Hasba Edukasi Mandiri, 2025)
In this digital era, easily accessible technology allows the public to easily obtain, read, and disseminate various types of information on social media. This study examines the Role of social media in the Dissemination of Information and the Enforcement of Law related to Alleged Domestic Violence (DV) Crimes in the digital era. Social media has become an important platform for raising public awareness, providing space for victims to report cases, and encouraging law enforcement. This study uses a normative juridical approach with an analysis of relevant legal regulations, such as Law Number 23 of 2004 on the Elimination of Domestic Violence (PKDRT) and the Electronic Information and Transactions Law (ITE Law). The results indicate that social media not only accelerates the dissemination of information but also helps domestic violence victims gain public support and legal evidence. However, it is important to consider legal and ethical boundaries in its use. This research recommends digital literacy and collaboration between the government and social media platforms to create a safe digital environment and support effective law enforcement.